Feeling like a student but thinking like a teacher: a study of the development of professional identity in initial teacher education - Flores, Maria Assunção (2020)
This paper draws upon a wider piece of research aimed at investigating professional identity development in initial teacher education. It is based upon the view of identity as a dynamic and multifaceted process and initial teacher education as a key context for its development. Data reported in this paper are part of a broader project carried out in Portugal and was collected through written narratives with 20 student teachers. In this paper findings arising from student teachers' accounts are presented, according to the main emerging themes: i) feeling like a student and thinking like a teacher; ii) confronting present and past experiences: inner tensions and dilemmas; iii) raising awareness of the complexity of the classroom context; iv) the teaching profession: aspirations and concerns of prospective teachers. Implications of the findings for initial teacher education are discussed.